2002
DOI: 10.1091/mbc.e02-05-0259
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Evolution of von Willebrand/Integrin A Domains: Widely Dispersed Domains with Roles in Cell Adhesion and Elsewhere

Abstract: The von Willebrand A (VWA) domain is a well-studied domain involved in cell adhesion, in extracellular matrix proteins, and in integrin receptors. A number of human diseases arise from mutations in VWA domains. We have analyzed the phylogenetic distribution of this domain and the relationships among approximately 500 proteins containing this domain. Although the majority of VWA-containing proteins are extracellular, the most ancient ones, present in all eukaryotes, are all intracellular proteins involved in fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
631
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(643 citation statements)
references
References 124 publications
11
631
0
1
Order By: Relevance
“…All b2 integrins form a functional heterodimer complex with integrin a subunits that recognize ligand binding via the vWA domain (Dickeson and Santoro, 1998). It is the vWA domains of the integrin subunits that show significant homology with the copine-I AD (Whittaker and Hynes, 2002). Therefore, perhaps one of the evolutionarily conserved functions of vWA domains is to associate with protease-containing protein complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All b2 integrins form a functional heterodimer complex with integrin a subunits that recognize ligand binding via the vWA domain (Dickeson and Santoro, 1998). It is the vWA domains of the integrin subunits that show significant homology with the copine-I AD (Whittaker and Hynes, 2002). Therefore, perhaps one of the evolutionarily conserved functions of vWA domains is to associate with protease-containing protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The C2Ds of copines contain aspartate residues important for calcium and phospholipid binding (Nalefski and Falke, 1996;Rizo and Sudhof, 1998). The AD shows similarity to proteins that contain the von Willebrand factor (vWF) domain referred to as the vWF A domain (vWA) protein superfamily (Whittaker and Hynes, 2002). Although the majority of vWA-containing proteins in higher eukaryotes is extracellular, the most evolutionally conserved vWA domains are intracellular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast the N-terminal non-collagenous domain 1 (NC-1) consists of several subdomains with high homologies to adhesion proteins. The C-terminal subdomain of NC-1 reveals high homology to von-Willebrand-factor A and is called von-Willebrand-factor-A like domain 2 (vWFA2) [3]. A schematic representation of a single Col7 a-chain forming a homotrimer is shown in Investigations have shown that vWFA2 plays a crucial role for binding to type I collagen but also for interactions with other components of the extracellular matrix [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on NMR resonance assignment secondary structure elements have Abbreviations: Col7, type VII collagen; EBA, epidermolysis bullosa acquisita; mFNIII-9, murine fibronectin-III-like domain 9; NC-1, non-collagenous domain 1; NMR, nuclear magnetic resonance; SPR, surface plasmon resonance; TALOS, torsion angle likelihood obtained from shift and sequence similarity; mvWFA2, murine von-Willebrand-factor-A-like domain 2; TSP-d 4 , 3-(trimethylsilyl)propionic acid-d 4 sodium salt been obtained with the program torsion angle likelihood obtained from shift and sequence similarity+ (TALOS)+ [9]. Additional information has been achieved by 3 J-H(N)-H(a)-coupling constants and hydrogen-deuterium exchange. The experimental data are in good agreement with a homology model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of α 2 ÎŽ-4 subunit, encoded by C ACNA2D4 , is mostly copious in non-neuronal cells apart from retinal neurons [36,37]. By bioinformatics, the proteins encoded by several other genes have been identified, and they share the similar structure with α 2 ÎŽ subunits [38], but have not been proved to function as calcium α 2 ÎŽ subunits. The α 2 ÎŽ-1 subunit plays a vital role in hypertensive vascular Ca V 1.2 channel properties [39,40].…”
Section: Molecular Basis Of L-type Calcium Channelmentioning
confidence: 99%